Comparative cytotoxicity of a glycolipopeptide biosurfactant from Lactobacillus plantarum and its derived silver nanoparticles against breast cancer cells - Zaid Mohammed Joodi Al-Janabi; Waseem Yousif M. Al-dulaimy; Maryam Hekmat Abdulateef; Aeshah Abbood Ahmed; Mohammed Kadhom (Medicine in Microecology, 2025)
The present study describes the green synthesis of silver nanoparticles (AgNPs) using a glycolipopeptide (GLP) biosurfactant produced by Lactobacillus plantarum, and evaluates their physicochemical characteristics and anticancer potential. The formation of AgNPs was visually confirmed by a color change and further characterized by UV–Vis, XRD, AFM, and TEM, revealing spherical particles ranging from 20 to 300 nm. Zeta potential analysis (−32.1 mV) confirmed strong colloidal stability. FTIR and GC-MS analyses identified key functional groups and bioactive compounds in the GLP, including fatty acids and lipopeptides responsible for both surface activity and biological effects. Surface tension (32.4 mN/m) and emulsification index (61.5 %) further validated the biosurfactant's amphiphilic nature. In vitro cytotoxicity assays against MCF-7 breast cancer cells demonstrated dose-dependent effects, with the GLP and AgNPs showing 60.59 % and 54.77 % inhibition, respectively, at 400 μg/mL. Their combination enhanced cytotoxicity to 69.14 % while maintaining minimal toxicity toward WRL-68 normal liver cells, indicating selective activity. Compared to doxorubicin (IC50 ≈ 0.98 μg/mL, SI ≈ 1.01), the green formulations displayed a higher selectivity index (SI ≈ 2.71). The enhanced cytotoxicity is likely attributed to reactive oxygen species (ROS) generation, apoptosis induction, and membrane disruption. Although our findings highlight the dual functionality of the GLP biosurfactant as both a nanoparticle stabilizer and a bioactive agent, further in vivo studies and mechanistic investigations are warranted to validate its potential in cancer therapy.